Native opportunities to stop hypertension: study protocol for a randomized controlled trial among urban American Indian and Alaska Native adults with hypertension - Sinclair, Ka’imi; Nguyen, Cassandra J.; Wetherill, Marianna S.; Nelson, Katie; Jackson, Alexandra M.; Taniguchi, Tori; Jernigan, Valarie Blue Bird; Buchwald, Dedra (Frontiers in Public Health, 2023)
Introduction American Indian and Alaska Native (AI/AN) adults experience disproportionate cardiovascular disease (CVD) morbidity and mortality compared to other races, which may be partly attributable to higher burden of hypertension (HTN). Dietary Approaches to Stop Hypertension (DASH) is a high-impact therapeutic dietary intervention for primary and secondary prevention of CVD that can contribute to significant decreases in systolic blood pressure (BP). However, DASH-based interventions have not been tested with AI/AN adults, and unique social determinants of health warrant independent trials. This study will assess the effectiveness of a DASH-based intervention, called Native Opportunities to Stop Hypertension (NOSH), on systolic BP among AI/AN adults in three urban clinics. Methods NOSH is a randomized controlled trial to test the effectiveness of an adapted DASH intervention compared to a control condition. Participants will be aged ≥18 years old, self-identify as AI/AN, have physician-diagnosed HTN, and have elevated systolic BP (≥ 130 mmHg). The intervention includes eight weekly, tailored telenutrition counseling sessions with a registered dietitian on DASH eating goals. Intervention participants will be provided 30 weekly and will be encouraged to purchase DASH-aligned foods. Participants in the control group will receive printed educational materials with general information about a low-sodium diet and eight weekly 30 grocery orders. All participants will complete assessments at baseline, after the 8-week intervention, and again 12 weeks post-baseline. A sub-sample of intervention participants will complete an extended support pilot study with assessments at 6- and 9-months post-baseline. The primary outcome is systolic BP. Secondary outcomes include modifiable CVD risk factors, heart disease and stroke risk scores, and dietary intake. Discussion NOSH is among the first randomized controlled trials to test the impact of a diet-based intervention on HTN among urban AI/AN adults. If effective, NOSH has the potential to inform clinical strategies to reduce BP among AI/AN adults. Clinical trials registration https://clinicaltrials.gov/ct2/show/NCT02796313, Identifier NCT02796313.